Fractured penis with concomitant urethral injury: a challenging presentation at a tertiary hospital in north-central Nigeria-case report and literature review - Oyibo, Ugbede E.; Metibaiye, Oluwatoyin B.; Akhaine, Julius O.; Onwukwe, John C. (International Journal of Advances in Medicine, 2023)
Fractured penis is reported as a traumatic rupture of the tunica albuginea by following blunt injury to an upright penis. Though a rare urological emergency due to blunt trauma to a turgid penis. The rupture of the tunica albuginea is often single involving either of the two corpora cavernosa; however concomitant urethral injury is an exceptionally infrequent condition requiring primary urethral anastomosis. Many of the patients are likely to have urethral strictures following surgery. Buccal mucosal graft is repeatedly used for substitution urethroplasty in urethral stricture management; however, its use is not commonly reported for immediate treatment in the background of fractured penis. Herewith is the report of a 33-year-old male with rupture of both corpora cavernosa, as well urethral rupture, after coitus. The urethral injury was repaired using buccal mucosal graft. At follow-up, patient did not encounter erectile or voiding issues. The implementation of this technique would go a long way at ameliorating the occurrence of urethral strictures in these subsets of patients, however there is still room for larger sample-sized prospective studies in the future. Consistent with our index case, surgery for the fractured penis is expedient with a view to conserving urethral and sexual function.